Analysis of The Dynamics and Structure of Credit Operations of PJSC "Moscow Industrial Bank" for 2017-2019 ("Journal "U". Economy. Management. Finance.", 2020)
This article analyzes the dynamics and structure of credit operations of PJSC "Moscow Industrial Bank" for the period from 2017 to 2019. Based on the results of the study, the main directions of improving the bank's lending operations were noted.